Pathogenicity and Characterisation of Newcastle Disease Virus Isolated in Iran - Kianizadeh, Mahdi (2002)
Nine Iranian Iranian Newcastle disease viruses were isolated from different Newcastle disease outbreaks during 1995 to 1999 across Iran. Characterization of the isolates was performed using three standard conventional methods such as mean death time (MDT), intracerebral pathogenicity index (ICPI) and intravenous pathogenicity index (IVPI) in embryonated specific pathogen free (SPF) chicken eggs, day old SPF chicks and 6-week old SPF chickens, respectively. Based on the overall results, all the nine Iranian isolates (MK7, MK12, MK1 3, MK14, Krd76, Kasra97, GH77, KH2/78 and ES 1/99) belong to velogenic pathotype. Following infection in 6-week old SPF chickens via intra-ocular route, regardless of the isolates, the infected chickens showed depression, ruffled feather and diarrhoea, ending in death. However, there were no obvious respiratory disorders. Meanwhile nervous signs were shown in chickens inoculated with four isolates (MK7, GH77, MK1 3 and Kasra97) at the later stage of the infection. Grossly, the initial lesions such as haemorrhage and enlargement were observed in visceral organs including proventriculus, intestine and spleen. No significant changes were observed in the respiratory system. However in some cases, chickens infected with some isolates (MK7, MK12, MK13, Kasra97, KH2178 and ES1/99) demonstrated limited congestion in the trachea and lungs. Microscopically, the earliest changes were observed in proventriculus, intestine, spleen and liver. Focal and diffuse haemorrhage (proventriculus and intestine), lymphoid depletion (spleen) and mononuclear cell infiltration (liver) were common features. Endotheliosis and malacia were seen in the brain. Based on the MDT results (39.6-56 hours) as well as the presence of lesions in the visceral organs, all the isolates can be grouped as viscerotrop velogenic Newcastle disease virus (WNOV) pathotype. The F protein cleavage site gene of all the nine isolates was amplified (242 bp) by RT-PCR and sequenced. Nucleotide and amino acid sequence analysis revealed that the cleavage site of all the isolates consisted of 2 pairs of basic amino acids (Arg) at positions 112, 113, 115 and 116 forming the motif 112RRQRR116, similar to motif in velogenic strains isolated from other countries. However, five amino acids substitutions were observed in isolate MK13 compared to other isolates of which 2 were in F1 N-terminal, 2 upstream and one downstream of the cleavage site. Two of the amino acids differences in MK13 located at positions 108 and 132 were not observed in published sequence of NOV strains. Hydropathy profiles were similar for all the isolates. They contained one major hydrophilic area at cleavage site and one major hydrophobic area extended between positions 117 to 142 corresponded to the F1 N-terminal. This feature of hydropathy profile is similar to that of virulent NDV strains. In phylogenetic analysis, all Iranian isolates are grouped together with other virulent strains in group C. The Russian virulent strain, VOL 95, showed the same amino acid sequence with all the Iranian isolates except MK13 indicating a common origin of the viruses. The importance of these substitution remain to be studied. Finally, based on the results obtained, this study proved that all nine Iranian NDV isolates belonged to the velogenic pathotype.